The Enhancement of Public Health Through Breast Self-Examination Health Education in Women of Childbearing Age - Wijayanti, Irfana Tri (Journal of Community Services and Engagement: Voice of Community (VOC), 2023)
Breast cancer is the cancer disease with the second highest prevalence after cervical cancer in Indonesia in 2013, also the prevalence of breast cancer is around 2.4% in Yogyakarta. Meanwhile in Central Java Province, the prevalence of breast cancer is around 0.5%. The aim of the community service is an effort to improve public health through health education about breast self-examination. The method of the community service is educations people through a classical study, question and answer as well as discussion and simulation. There were findings of 85% abnormalities in the breasts and no self-handlers were treated. The provision of health education to couples of childbearing age can help women to develop knowledge, attitudes, and behaviors in preventing breast cancer with one of the efforts to do self-examination.